The genus Alphocoris in the Indomalaya (Hemiptera: Heteroptera: Scutelleridae) - Rédei, Dávid; Tsai, Jing-Fu; Jindra, Zdeněk (Zootaxa, 2018)
The Indomalayan species of the genus Alphocoris Germar, 1839 (Hemiptera: Heteroptera: Scutelleridae: Odontotarsinae: Odontotarsini) are revised. Three species, A. caudatus Rédei, Tsai & Jindra, sp. nov. (India: Maharashtra), A. naso Rédei & Tsai, sp. nov. (India: Goa), and A. asper Rédei, Tsai & Jindra, sp. nov. (India: Goa and Maharashtra), are recognized. The type material of A. lixoides Germar, 1839 (type locality: Senegal) is documented; previous records of this species from India and Pakistan are considered as based on misidentifications, the species is restricted to the Afrotropical Region.